Waqf administration under Majlis Agama Islam dan Adat Melayu Perak ; a paradigm shift : case study on Wakaf Masjid Melayu Taiping, Perak, Malaysia / Mudirah Shaharudin, Noraini Johari and Mohd Salim Jasiman - Shaharudin, Mudirah; Johari, Noraini; Jasiman, Mohd Salim (2012)
The main purpose of this paper is to discuss the performance and problems of the Waqf administration of Wakaf Masjid Melayu Taiping in Perak , Malaysia under the Majlis Agama Islam and Adat Melayu Perak. This paper first describes the problems of Waqf Masjid Melayu Taiping and then suggests proposals for improvement. Waqf administration requires a paradigm shift and new innovative avenues. It also needs to develop a hybrid viable model for generating more benefits for all involving parties of the society with sustainability characteristics. It is recognized that there is no ample study in the area of Waqf. Further, literature is very scanty relating to the Waqf administration. The exiting studies identify various facets of the Waqf and its administration issue to explore different aspects of theoretical dimensions and practices.